Russian gender linguistics forced to respond can women be made visible in communication? (with examples from Polish, Czech, and Slovenian) - Scheller-Boltz, Dennis (Видавництво Львівської політехніки, 2015)
This paper deals critically with current methodological approaches in Russian gender linguistics. It will be shown that we need to introduce and apply other approaches to further gender linguistic research in order to make gender analyses more proper and effective and, consequently, to achieve new and fruitful research results. In this context, my paper can be considered as a form of appeal to Russian gender linguists to question critically the predominant androcentrism in language. In the future, discourses need to be shaped in a different manner and possibilities must be provided to guarantee a diversity of gender and identity in society as well as in language. Using the example of the entity “woman” or, accordingly, of the visibility of women in language, I will point out that one cannot reduce (her) visibility in its narrow sense to be visible for the eyes’, because visibility can also relate to cognitive structures, perception, and gender construction. In the following, I will not provide any suggestions for concrete linguistic solutions. Rather it is my aim to examine different linguistic subdisciplines in order to demonstrate that they influence the visibility of women in language and, moreover, to illustrate their impact in the existence, the perception and the construction of women in communication.
Keywords: Russian gender linguistics; discourse; structuralism; structuralism; post-structuralism; motion suffixes; women and language